Composite solid electrolyte based on (Ca2+, Al3+)-infiltrated ZrO2(MgO) for direct sulfur determination in the liquid iron. (September 2022) - Wen, T.P.; Jin, Y.; Yuan, L.; Yan, Z.G.; Liu, Z.Y.; Yu, J.K.
Abstract: Magnesium-stabilized zirconia [ZrO2 (MgO)] with calcium aluminate (CaO–Al2 O3 ) ceramic composite electrolyte based on (calcium ion [Ca 2+ ], aluminum ion [Al 3+ ])-infiltrated zirconia-magnesia [ZrO2 (MgO)] porous backbone was prepared for direct sulfur ([S]) determination in the liquid iron. Effect of amylum content on the phase composition, microstructures and mechanical properties of the composite electrolyte was detected and correlated to the electrochemical performance. The results indicated that the ZrO2 (MgO)-(CaO–Al2 O3 ) composite electrolyte simultaneously inherited the mechanical and electrochemical properties of ZrO2 (MgO), and unique physical and chemical properties of CaO–Al2 O3 . The compressive strength of the composite electrolyte reached above 250 MPa and the conductivity reached up to 0.003 S/cm -, meeting the requirements of the sensor for the electrolyte. The assembled sensor could respond to sulfur activity and showed fine response characteristics. Among the tested compositions, the composite electrolyte with 6.0 wt% of amylum added in ZrO2 (MgO) porous backbone exhibited the best properties and was more suitable for application in sulfur determination. Highlights: A novel composite electrolyte for direct sulfur determination by infiltrating Ca 2+ and Al 3+ into porous ZrO2 (MgO) backbone. Phase composition and microstructure of composite electrolyte are correlated to their electrochemical performance. It implies a potential method for design metallurgical sensor.